Genetic identification and structure of Clarias batrachus (Linnaeus, 1758) from Southeast Asia using a mitochondrial DNA marker - Lee, Paolin; Sulaiman, Zohrah (Zootaxa, 2015)
A phylogenetic tree and median-joining network based on cytochrome b sequence data revealed clades consistent with morphological differences and geographical distribution of Clarias batrachus (Linnaeus, 1758) in Southeast Asia. AMOVA analysis for variation was significant among populations (P<0.05) and was in agreement with morphological differences. Pairwise differences were significant between Java and Brunei/Borneo, Brunei/Borneo and west Malaysia, and Java and west Malaysia samples (P < 0.05). Closest relationships were found between samples from Brunei/Borneo and Java, and between west Malaysia and Laos-Sumatra. Nine haplotypes were unique to geographical regions. The Java species had high haplotype (1.000 ± 0.126) but low nucleotide (0.017) diversities, suggesting a population bottleneck followed by expansion. However, SSD and Hri (P=0.5) did not support demographic expansion. Instead, purifying selection where mutations occur and accumulate at silent sites is a more acceptable explanation.